KONDISI PRILAKU SOSIAL SISWA BERKEBUTUHAN KHUSUS DI SMPN 6 BUKITTINGGI - Silfi Maya Dwita; Yeni Afrida; Sri Hidayati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Everyone has growth and development in the span of his life. There are those who are normal and there are also those who are not normal, it can be said that those who are not normal are those who have special needs. Children with special needs are children who have unique and different characteristics from children in general. Children with special needs have different social behavior because it depends on the social interactions of the people around them. The purpose of this research is to increase knowledge and insight and to find out the condition of social behavior of children with special needs. With that conducted research with qualitative descriptive method by collecting data, namely observation and interviews. Data analysis techniques with data reduction, data display and data verification. The results of this study are that the behavior of children with special needs is caused by family factors, biological factors, and sociology.